Do Patients With Parkinson's Disease With Freezing of Gait Respond Differently Than Those Without to Treadmill Training Augmented by Virtual Reality?. (May 2020) - Bekkers, Esther M. J.; Mirelman, Anat; Alcock, Lisa; Rochester, Lynn; Nieuwhof, Freek; Bloem, Bastiaan R.; Pelosin, Elisa; Avanzino, Laura; Cereatti, Andrea; Della Croce, Ugo; Hausdorff, Jeffrey M.; Nieuwboer, Alice
Background . People with Parkinson's disease and freezing of gait (FOG+) have more falls, postural instability and cognitive impairment compared with FOG−. Objective . To conduct a secondary analysis of the V-TIME study, a randomized, controlled investigation showing a greater reduction of falls after virtual reality treadmill training (TT + VR) compared with usual treadmill walking (TT) in a mixed population of fallers. We addressed whether these treadmill interventions led to similar gains in FOG+ as in FOG−. Methods . A total of 77 FOG+ and 44 FOG− were assigned randomly to TT + VR or TT. Participants were assessed pre- and posttraining and at 6 months' follow-up. Main outcome was postural stability assessed by the Mini Balance Evaluation System Test (Mini-BEST) test. Falls were documented using diaries. Other outcomes included the New Freezing of Gait Questionnaire (NFOG-Q) and the Trail Making Test (TMT-B). Results . Mini-BEST scores and the TMT-B improved in both groups after training ( P = .001), irrespective of study arm and FOG subgroup. However, gains were not retained at 6 months. Both FOG+ and FOG− had a greater reduction of falls after TT + VR compared with TT ( P = .008). NFOG-Q scores did not change after both training modes in the FOG+ group. Conclusions . Treadmill walking (with or without VR) improved postural instability in both FOG+ and FOG−, while controlling for disease severity differences. As found previously, TT + VR reduced falls more than TT alone, even among those with FOG. Interestingly, FOG itself was not helped by training, suggesting that although postural instability, falls and FOG are related, they may be controlled by different mechanisms.